การวิเคราะห์ชั้นฟิล์มบนผิวเหล็กกล้าไร้สนิมออสเทนิติกและเฟอริติกที่ผสมโครเมียมและนิกเกิลด้วยเอ็กซ์พีเอส - สาริษฐ์ ชัยกิตติศิลป์ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
This work investigates the surface film of ferritic and austenitic stainless steels, which has chromium contents of 20 - 39 Wt% and nickel contents of 4 - 29 Wt%, after exposure in air 24 h by XPS technique. The surface films of both stainless steel grades are similar, which compose of 2 layers: the chromium hydroxide and chromium oxide layers. The chromium oxide layer can be divided to be 2 layers: the chromium and iron oxide with iron, and the chromium oxide with chromium, iron and nickel layers. The thickness of chromium oxide layer decrease as the chromium contents in alloy increase, but the thickness of the chromium and iron oxide layer with iron increase. The relation between chromium contents and the thickness of the chromium and iron oxide layer with iron look like the S curve of that between chromium contents and pitting potentials. It may be said that the pitting corrosion resistant of stainless steels depends on the thickness of the chromium and iron oxide layer with iron. Nickel may participatein the chromium oxide layer. Generally, the possibility to detect nickel in the chromium oxide layer is higher in austenitic stainless steels than in ferritic stainless steels. The surface film contained nickel may increase the corrosion resistant of stainless steels.